MINORITAS MUSLIM DI INDIA - Reni Maulana Putri Reni (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This paper aims to discuss the history of Islamic minorities in India. The Muslim minority in India, it can be said that the development of Islam there is still facing big obstacles and challenges from Hindu groups, Hindus are very well known for their caste system from the highest caste to the lowest caste, for the lowest caste they give To the Muslims who were there, who were very influential in their social life, it was clear that the treatment of the Hindus towards the Muslim minority was only underestimated. In the political field there are only very few opportunities for Muslims, the remaining 1% is controlled by Hindus, while in the field of education, Muslim children are very far below even many who are illiterate, this is influenced by the Muslim minority economy. there which is very concerning and also the lack of assistance from the government, because they are Muslims it is very difficult to find work, they even disguise themselves by wearing Hindu clothes in order to get a job to meet their needs.